2012
DOI: 10.1089/scd.2011.0597
|View full text |Cite
|
Sign up to set email alerts
|

Increased Differentiation Capacity of Bone Marrow-Derived Mesenchymal Stem Cells in Aquaporin-5 Deficiency

Abstract: Mesenchymal stem cells (MSCs) are adult stem cells with a self-renewal and multipotent capability and express extensively in multitudinous tissues. We found that water channel aquaporin-5 (AQP5) is expressed in bone marrow-derived MSCs (BMMSCs) in the plasma membrane pattern. BMMSCs from AQP5 -/ -mice showed significantly lower plasma membrane water permeability than those from AQP5 + / + mice. In characterizing the cultured BMMSCs from AQP5-/ -and AQP5 + / + mice, we found no obvious differences in morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
(60 reference statements)
1
14
0
Order By: Relevance
“…2 ). Immunofluorescence studies of these BAL-derived cells demonstrated expression of the MSC marker CD105, the mesenchymal cell marker vimentin and the water channel aquaporin-5 (AQP5) as previously described for bone marrow-derived MSCs 29 ( Fig. 2 ).…”
Section: Resultssupporting
confidence: 52%
“…2 ). Immunofluorescence studies of these BAL-derived cells demonstrated expression of the MSC marker CD105, the mesenchymal cell marker vimentin and the water channel aquaporin-5 (AQP5) as previously described for bone marrow-derived MSCs 29 ( Fig. 2 ).…”
Section: Resultssupporting
confidence: 52%
“…For instance, sweat shows acidic pH levels, between 4.6 and 5.4 [56], and in the skin the protective sweat acid mantle acidity ranges from 4 to 5.5 [56]; the pH of human stomach is highly acidic, usually from 1 to 2; osteoclasts’ acidic microenvironment below pH 5.5 is critical for the bone resorption [57]; an acidic pH luminal fluid microenvironment is important for sperm maturation [58]. Interestingly, AQP5 was found expressed in sweat glands [59], gastric mucosa [60], bone cells [61], and in the epididymis [58]. In all these tissues, effective mechanisms of water flux regulation induced by pH fluctuations might be advantageous to prevent excessive water reabsorption and control cell volume and shape.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, many studies focused attention on the possible involvement of aquaporins (AQPs), a family of proteins characterized for their particular ability to regulate water and solute trafficking along membrane, with tumor progression [ 8 ]. Recent findings demonstrated that water homeostasis regulated by aquaporins represents an important mechanism at the basis of numerous processes such as cancer cell differentiation [ 9 , 10 ] and proliferation as well as apoptosis [ 11 ]. Moreover, aquaporins seem to be involved in tumor cell migration [ 12 ] and thus, in tumor spread and metastasis because of their sensitivity to changes in extracellular osmolality [ 13 ].…”
Section: Introductionmentioning
confidence: 99%